Association between Personal Hygiene, Personal Protective Equipment Usage, and Exposure Duration with the Occurrence of Allergic Contact Dermatitis among Seaweed Farmers - Dian Furqani Hamdan; Rifkha Ayu Andira; Rini Faramita Sadar (CV. Social Politic Genius (SIGn), 2025)
Seaweed farmers in coastal areas face a high occupational risk of allergic contact dermatitis due to persistent exposure to aquatic environments. This study aimed to analyze the determinants of this skin disease by evaluating its association with personal hygiene levels, compliance with personal protective equipment (PPE) usage, and exposure duration. A quantitative, analytical cross-sectional design was employed, involving 47 respondents selected via simple random sampling based on strict inclusion and exclusion criteria. Primary data were collected through a validated questionnaire and physical examinations, followed by Chi-square analysis at a 0.05 significance level. The results indicated a dermatitis prevalence of 55.32% among the sample. Poor personal hygiene (p = 0.003) and inadequate compliance with PPE usage (p = 0.016) were identified as significant determinants of the disease. Interestingly, analysis of the work duration revealed an anomaly: the group with less than 8 hours of daily contact exhibited the highest morbidity rate (p < 0.001), suggesting a potentially strong influence of individual genetic susceptibility and seawater contamination. Based on these findings, local primary healthcare authorities should implement targeted educational programs on behavioral modification and facilitate the construction of clean-water rinsing facilities to effectively interrupt the pathogen transmission chain.